2012
DOI: 10.1159/000340012
|View full text |Cite
|
Sign up to set email alerts
|

Non-Islet Cell Tumor Hypoglycemia at the Second Recurrence of Malignant Solitary Fibrous Tumor in the Retroperitoneum and Pelvis: A Case Report

Abstract: An 83-year-old man underwent complete resection of a large malignant solitary fibrous tumor in the retroperitoneum in 2006 and of a local recurrent tumor in 2010. In 2011, he was admitted to our hospital because of hypoglycemia. His serum glucose level was very low, and his levels of insulin and C-peptide were low. Furthermore, he had a recurrent tumor in the retroperitoneum and pelvis. Immediately after the third surgery for complete resection, he had no hypoglycemic episodes and his serum glucose level was w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Several studies have confirmed the secretion of HMW-IGF-II using immunoblotting analyses of perioperative serum [ 15 , 22 , 23 ]. In the present case, an immunoblotting analysis revealed that the strong band of HMW-IGF-II in the preoperative serum had disappeared after tumor resection, which is compatible with the clinical improvement of hypoglycemia after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed the secretion of HMW-IGF-II using immunoblotting analyses of perioperative serum [ 15 , 22 , 23 ]. In the present case, an immunoblotting analysis revealed that the strong band of HMW-IGF-II in the preoperative serum had disappeared after tumor resection, which is compatible with the clinical improvement of hypoglycemia after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Low IGF-I levels in patients with NICTH are attributed to chronic attenuation of GH secretion, due to the negative feedback of IGF-II ( 9 ). Several studies have shown that NICTH due to HMW-IGF-II can be diagnosed using western blot analysis ( 10 12 ). Hata et al ( 10 ) examined HMW-IGF-II by using preoperative and postoperative blots and demonstrated that HMW-IGF-II disappeared postoperatively, which is considered to be a useful therapeutic index.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that NICTH due to HMW-IGF-II can be diagnosed using western blot analysis ( 10 12 ). Hata et al ( 10 ) examined HMW-IGF-II by using preoperative and postoperative blots and demonstrated that HMW-IGF-II disappeared postoperatively, which is considered to be a useful therapeutic index. In the present case, perioperative western blot analysis was also performed, which revealed the disappearance of HMW-IGF-II, but also the appearance of several unidentified protein bands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SFT in the retroperitoneum is rare, and 31 cases have been reported including this case for the last 15 years [ 9 , 14 , 16 , 18 , 20 24 , 26 42 ] (Table 1 ). The English language literature was extracted from PubMed from 2000 to 2015 using the following Medical Subject Heading terms: “solitary fibrous tumor” and “retroperitoneum”.…”
Section: Case Presentationmentioning
confidence: 99%